[Outpatient care and disease burden of rheumatoid arthritis : Results of a linkage of claims data and a survey of insured persons] - Albrecht, K.; Luque Ramos, A.; Callhoff, J.; Hoffmann, F.; Minden, K.; Zink, A. (Z Rheumatol, 2018)
BACKGROUND: Healthcare of patients with rheumatoid arthritis (RA) in Germany has mainly been evaluated in the past in RA cohorts from specialized arthritis centers. This study investigated rheumatological care on a population basis, using claims data from a nationwide statutory health insurance fund (BARMER GEK) in combination with patient-reported outcomes from a questionnaire survey of insured persons with RA. METHODS: Data from insurants aged 18-79 years with M05 (seropositive RA) or M06 (other RA, ICD-10) diagnoses were analyzed concerning diagnostics, medication and prescribing physician. A 31-item questionnaire covering patient reported diagnosis, healthcare utilization and burden of illness was sent to a stratified random sample of 6193 insured persons. Data from the respondents regarding rheumatological care and disease status were evaluated. RESULTS: In 2013 and 2014, a total of 96,921 adults with M05 or M06 diagnosis were insured. The questionnaire was answered by 51% of the sample and of these 81% confirmed the RA diagnosis. RA had been diagnosed by a rheumatologist in 59% of the cases, 70% reported moderate to severe pain and 46% had functional disability. Between at least 40% (claims data) and up to 68% (respondents) were in specialized rheumatological care. Treatment with disease-modifying antirheumatic drugs (DMARDs) was 61% (claims data) and 63% (respondents) in persons in rheumatological care but only 18% outside rheumatological care. CONCLUSION: The results indicate that specialized rheumatological care is required to provide adequate treatment for patients with RA in Germany. Patients with higher age and patients with M06 diagnosis had less drug prescriptions and were less frequently treated by rheumatologists.